Contraindications to immunotherapy: a global approach. Issue 1 (11th September 2019) - Pitsios, C.; Tsoumani, M.; Bilò, M. B.; Sturm, G. J.; Rodríguez del Río, P.; Gawlik, R.; Ruëff, F.; Paraskevopoulos, G.; Valovirta, E.; Pfaar, O.; Calderón, M. A.; Demoly, P.
Abstract: Background: Recommendations on contraindications to allergen immunotherapy (AIT) have been independently developed by National and International Societies/Academies. AIT contraindications are mainly based on case reports, case‐series, or experts' opinion, while evidence‐based information is limited. The aim of the present review was to describe existing guidelines on contraindications to AIT and to highlight differences between them. Main body: An extended review of the literature regarding contraindications to AIT for respiratory allergy and venom hypersensitivity was performed. Furthermore, Societies and Academies registered in the World Allergy Organization and EAACI databases, were asked for additional information. Only AIT guidelines published under official auspicies were included. A large heterogeneity among the various recommendations on contraindications was registered. Common contraindications to most of the guidelines were: lack of adherence, pregnancy before the start of AIT, the use of beta‐blockers, certain age groups, uncontrolled asthma, autoimmune diseases and malignancies. Conclusion: As new data arise, revisions might soon be needed allowing AIT in the cases of patients treated with ACE inhibitors and beta‐blockers, in elderly patients and in patients with concomitant autoimmune diseases and neoplasias in remission. The decision to prescribe AIT is always tailor‐made, balancing risk vs benefit. Creating globally accepted guidelines would help Allergologists in their decision making.